Progressive Pseudorheumatoid Dysplasia resolved by whole exome sequencing: a novel mutation in WISP3 and review of the literature - Ben Pode-Shakked; Asaf Vivante; Ortal Barel; Shai Padeh; Dina Marek-Yagel; Alvit Veber; Shachar Abudi; Aviva Eliyahu; Irit Tirosh; Shiri Shpilman; Shirlee Shril; Friedhelm Hildebrandt; et al. (BMC, 2019)
Abstract Background Progressive pseudorheumatoid dysplasia (PPRD) is a rare autosomal-recessive, non-inflammatory arthropathy, shown to be caused by mutations in the WNT1-inducible signaling pathway protein 3 (WISP3) gene. Although several hundred cases were reported worldwide, the diagnosis remains challenging. Subsequently, the syndrome is often unrecognized and misdiagnosed (for instance, as Juvenile Idiopathic Arthritis), leading to unnecessary procedures and treatments. The objective of the current study was to identify the molecular basis in a family with PPRD and describe their phenotype and course of illness. Patients and methods We present here a multiply affected consanguineous family of Iraqi-Jewish descent with PPRD. The proband, a 6.5 years old girl, presented with bilateral symmetric bony enlargements of the 1st interphalangeal joints of the hands, without signs of synovitis. Molecular analysis of the family was pursued using Whole Exome Sequencing (WES) and homozygosity mapping. Results WES analysis brought to the identification of a novel homozygous missense mutation (c.257G > T, p.C86F) in the WISP3 gene. Following this diagnosis, an additional 53 years old affected family member was found to harbor the mutation. Two other individuals in the family were reported to have had similar involvement however both had died of unrelated causes. Conclusion The reported family underscores the importance of recognition of this unique skeletal dysplasia by clinicians, and especially by pediatric rheumatologists and orthopedic surgeons.